2010
DOI: 10.1007/s00430-009-0141-6
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Borrelia burgdorferi in endomyocardial biopsies in patients with new-onset unexplained dilated cardiomyopathy

Abstract: Dilated cardiomyopathy (DCM) represents the third most common cause of heart failure and the most frequent cause of heart transplantation. Infectious, mostly viral, and autoimmune mechanisms, together with genetic abnormalities, have been reported as three major causes of DCM. We hypothesized that Lyme disease (LD), caused by spirochete Borrelia burgdorferi (Bb), might be an important cause of new-onset unexplained DCM in patients living in a highly endemic area for LD such as the Czech Republic. We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 19 publications
2
29
0
4
Order By: Relevance
“…In a pilot study from our centre, we have reported a 21% prevalence of Bb in EMB specimens obtained from 39 patients with recent-onset DCM (ref. 5 ). Similar findings were subsequently published by other Czech authors 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pilot study from our centre, we have reported a 21% prevalence of Bb in EMB specimens obtained from 39 patients with recent-onset DCM (ref. 5 ). Similar findings were subsequently published by other Czech authors 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Within the endemic region of Central Europe there is increasing evidence that Borrelia burgdorferi (Bb) may be associated with the development of DCM (ref. [5][6][7] ). To further support a causal relationship between the presence of Bb in the heart muscle and the development of DCM, demonstration of the absence of Bb in the myocardium of subjects with normal left ventricular (LV) systolic function is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the data currently available do not provide conclusive evidence of the effect of this antibiotic regimen on prevalence of Borrelia burgdorferi in patients recently diagnosed with DCM as compared with controls (in [22]: in 24% Borrelia genome detectable in myocardial biopsy specimens versus 0% in the control group). While Palacek et al (31) observed a significant improvement of left ventricular function under antibiotic treatment in their patient population which tested positive for Borrelia genome, Kubanek et al (22) found no positive response to this therapy.…”
Section: Chronic Coursementioning
confidence: 96%
“…While the same work group (29) demonstrated an increased prevalence of Borrelia antibodies in patients with DCM, this correlation could not be confirmed in later studies by Levolas (30) and Rees (e11). The latest studies (22,31), using a highly sensitive PCR method, found a significantly higher genome Figure 4: Cardiac magnetic resonance imaging with 4-chamber view a) of a patient with Lyme carditis along with first-degree AV block and complete left bundle-branch block: after gadolinium administration, multilocular lateenhancement (LE), situated subepicardially, mid-myocardially and subendocardially. b) In the short-axis view, LE is primarily situated in the midmyocardium; however, the septum is also affected, possibly the substrate of the affected conduction system (yellow arrow).…”
Section: Chronic Coursementioning
confidence: 99%
“…Non-viral infections as the cause of myocarditis are uncommon in our region, although in some endemic areas of the Czech Republic, Borrelia burgorferi is relatively often detected in recent onset dilated cardiomyopathy (RODCM) (ref. [18][19][20] ). Other possible causes of myocarditis are autoimmune or toxic factors.…”
Section: Introductionmentioning
confidence: 99%